004 Does the use of the A&E theatre reflect the demise in the surgical skills of the emergency physician?. (14th September 2011) - Cooper, J; Hannah, J; Brown, W
Abstract : Objectives and Backgrounds: The College of Emergency Medicine has evolved from the Casualty Surgeons Association formed in 1967. At that time most of the expertise in the Accident and Emergency (A&E) Department was surgical and consequently many Departments had an operating theatre in which to carry out a variety of procedures. From this background the specialty of Emergency Medicine (EM) has arisen and developed. Many Departments no longer use, or have lost, their theatre as the workload and expertise has become more medical in nature. However, sound basic surgical skills are very important to the modern Emergency Physician and many feel these are still best taught in theatre. To date the Emergency Department of Aberdeen Royal Infirmary (ARI) has retained the use of its theatre and therefore to the training opportunity it provides. This study aimed to evaluate the number and type of cases passing through this facility to study trends and to evaluate what the future may be for the A&E theatre. Methods: This was a retrospective cohort study of the A&E theatre usage in ARI, a large teaching hospital in the North East of Scotland from 1995 to 2010. Cases were identified from theatre log books, relevant demographics extracted and analysed. Results: A total of 8785 procedures were performed during the study period of which the most common were fracture manipulation, abscess drainage and foreign body removal. There was a steady decline in theatre usage: 1078 cases in 1995; 828 cases in 2000; 368 cases in 2005 and only 214 cases in 2010. The reduction was most dramatic in the number of wrist fractures manipulated and in the number of perianal and pilonidal abscess operated on. Conclusions: Use of the A&E theatre is reducing. The reasons for this are complex and include: changing surgical practices; reduced anaesthetic presence in remote sites within the hospital and, most importantly, the change in the skill mix of the staff in the Emergency Department. Sound General Surgical and Orthopaedic basic surgical skills are valuable to the Emergency Physician but experience in these specialties is no longer required in EM training. Thought should be given to whether these skills could be learnt in the A&E theatre before such facilities disappear completely.